Molecular interactions of trichoderma β-1,4-glucosidase (ThBglT12) with mycelial cell wall components of phytopathogenic Macrophomina phaseolina - Mohammad Hood, Mohammad Hakim; Tengku Abdul Hamid, Tengku Haziyamin; Abdul Wahab, Roswanira; Huyop, Fahrul Zaman; Kaya, Yilmaz; Abdul Hamid, Azzmer Azzar (Taylor & Francis, 2022)
Efficacy of a β-1,4-glucosidase from Trichoderma harzianum T12 (ThBglT12) in disrupting the cell wall of the phytopathogenic fungus M. phaseolina (Macrophomina phaseolina) was studied, as the underlying molecular mechanisms of cell wall recognition remains elusive. In this study, the binding location identified by a consensus of residues predicted by COACH tool, blind docking, and multiple sequence alignment revealed that molecular recognition by ThBglT12 occurred through interactions between the α-1,3-glucan, β-1,3-glucan, β-1,3/1,4-glucan, and chitin components of M. phaseolina, with corresponding binding energies of −7.4, −7.6, −7.5 and −7.8 kcal/mol.